2006
DOI: 10.1080/17450390600785525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betaine and condensed molasses solubles on nitrogen balance and nutrient digestibility in piglets fed diets deficient in methionine and low in compatible osmolytes

Abstract: A balance experiment was carried out to investigate the effects of betaine monohydrate (BET) or betaine derived from condensed molasses solubles (CMS) as a substitute for methionine and choline on nitrogen (N) balance and total tract nutrient digestibility in weaned piglets. The experiment included four treatments with 32 barrows with an average initial body weight (BW) of 13.5 kg. The supplementation of DL-methionine and choline (positive control = PC) to the basal diet, which was deficient in methionine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
3
34
0
1
Order By: Relevance
“…Since pigs in general lack fiber degrading enzymes, these results indicate that betaine has the potential t o stimulate bacterial fermentation of dietary fiber in the gastrointestinal tract. It has been suggested that intestinal bacteria may have a requirement for compatible osmolytes such as betaine (Eklund et al, 2005;2006a;b). I n accordance w i t h a trend towards increased CF digestibility, supplementation of betaine to the assay diet increased ileal SCFA concentrations by 77.6 mmolkg DM compared with the control treatment (P<0.05), indicating intensified bacterial activity in the small intestine.…”
Section: Resultsmentioning
confidence: 48%
See 4 more Smart Citations
“…Since pigs in general lack fiber degrading enzymes, these results indicate that betaine has the potential t o stimulate bacterial fermentation of dietary fiber in the gastrointestinal tract. It has been suggested that intestinal bacteria may have a requirement for compatible osmolytes such as betaine (Eklund et al, 2005;2006a;b). I n accordance w i t h a trend towards increased CF digestibility, supplementation of betaine to the assay diet increased ileal SCFA concentrations by 77.6 mmolkg DM compared with the control treatment (P<0.05), indicating intensified bacterial activity in the small intestine.…”
Section: Resultsmentioning
confidence: 48%
“…Similarly, supplementation of betaine originating from condensed molasses solubles and betaine monohydrate, included at a level of 2.5 g or 3.0 g per kg diet, increased ileal and (or) t o t a l tract NDF and ADF digestibilities (Eklund et al, 2006a;b). Since pigs in general lack fiber degrading enzymes, these results indicate that betaine has the potential t o stimulate bacterial fermentation of dietary fiber in the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations